Tindakan Meningkatkan Keaktifan Siswa dalam Pembelajaran PPKn melalui Metode Diskusi Kelompok di SMP Negeri 5 Takengon - Leni Erliana; Amin Al Masyhuri; Shalahuddin Al Ayyubi; Mawaddah Mawaddah; Mulyani Ulan Dari (Jurnal Pendidikan dan Sastra Inggris, 2025)
This study aims to increase student engagement in the Pancasila and Citizenship Education (PPKn) subject by implementing a group discussion learning strategy. The background of the study stems from the low level of student engagement in the PPKn learning process, which results in the suboptimal instillation of important values, such as nationalism, democratic principles, and a sense of responsibility as citizens. In fact, the main goal of PPKn learning is to shape individuals with character, critical thinking, and the ability to implement the values ​​of friendship in everyday life. The method used in this study is a qualitative descriptive approach with data collection techniques in the form of literature studies. Through literature analysis, it is clear that the group discussion strategy provides space for students to actively express, study ideas, and criticize a problem. This is in line with the characteristics of PPKn which requires a dialogic and participatory process in learning. The research findings indicate that the implementation of group discussions can increase student motivation and active involvement, strengthen social interaction, and help deepen understanding of PPKn material. In addition, group discussions also contribute to the development of communication skills, cooperation abilities, and mutual respect among students. This skill is highly relevant in the context of civics education, which emphasizes not only cognitive aspects but also affective and social aspects. However, implementing group discussions also faces several obstacles, such as unequal distribution of tasks, domination by some students, and violations of control over the discussion. Possible solutions include group rotation, assigning individual responsibilities, and using more creative learning media. With careful planning, this strategy has proven effective in creating an active, inclusive, and enjoyable learning environment, enabling more effective achievement of Civics learning objectives.